Clarifying inconclusive functional analysis results: Assessment and treatment of automatically reinforced aggression. Issue 2 (17th April 2015) - Saini, Valdeep; Greer, Brian D.; Fisher, Wayne W.
<x xml:space="preserve">Abstract</x> We conducted a series of studies in which multiple strategies were used to clarify the inconclusive results of one boy's functional analysis of aggression. Specifically, we (a) evaluated individual response topographies to determine the composition of aggregated response rates, (b) conducted a separate functional analysis of aggression after high rates of disruption masked the consequences that maintained aggression during the initial functional analysis, (c) modified the experimental design used during the functional analysis of aggression to improve discrimination and decrease interaction effects between conditions, and (d) evaluated a treatment matched to the reinforcer hypothesized to maintain aggression. An effective yet practical intervention for aggression was developed based on the results of these analyses and from data collected during the matched‐treatment evaluation.